Differential symptomatology and prevention of permanent complications dependent on localisation of osteochondroma - Gałązka, Przemysław; Reszczyńska-Domagała, Marika; Redloch, Krzysztof; Ratajczak, Przemysław; Marjańska, Agata; Styczyński, Jan; Daniluk-Matraś, Irena (Pediatria Polska - Polish Journal of Paediatrics, 2018)
Osteochondroma is the most common benign bone tumour in children and usually occurs in the metaphyseal region of the long bones, being responsible for over 40% of all bone tumours and tumour-like lesions. The objective of this paper is the presentation of a series of cases of children with osteochondroma with different localisation and clinical presentation. Variability of localisation resulted in differential approach and prevention of permanent complications. Total surgical en bloc excision of the adjacent osteochondroma is considered as the treatment of choice. Symptoms related to an osteochondroma are usually relieved by the surgery. Major complications and local recurrence are rare. The general surgical indications for benign bone growths are cosmetic defect, exostosis in a location at risk to repetitive trauma, increased risk of the exostoses to fracture, neurological involvement, impairment of the articular range of motion, and suspicion of malignancy.